The impact of exposure to HPV related information and injunctive norms on young women's intentions to receive the HPV vaccine in China: A structural equation model based on KAP theory - Wang, Yi; Chen, Yubing; Bao, Sheng (Frontiers in Public Health, 2023)
Background: The HPV vaccination is a crucial line of defense against cervical cancer. As a result of government support and positive publicity from the majority of media, a craze for HPV vaccination has occurred in China. Besides, the intention to get the HPV vaccine among women of appropriate age is also influenced by families’ and friends’ attitudes and perceptions towards HPV vaccine. Therefore, the purpose of this study was to investigate how HPV related information exposure and injunctive norms affect young Chinese women’s intentions to receive the HPV vaccine. Methods: A structural equation model was developed based on KAP theory, and 567 effective questionnaires were collected through an online survey. We used SPSS 26.0 for the reliability and validity analysis and the differential testing of demographic characteristics, and Amos 26.0 for the goodness-of-fit analysis and paths testing of the model. Results: Our findings showed that (1) intention to receive HPV vaccine differed significantly in age (P=0.046), educational background (P = 0.001), and occupation (P = 0.004). (2) Exposure to HPV related information positively affected knowledge about HPV (β = 0.316, P < 0.001) and intention to receive HPV vaccine (β = 0.141, P < 0.001). (3) Knowledge about HPV positively affected attitude towards HPV vaccine (β=0.341, P<0.001), but negatively affected intention to receive HPV vaccine (β=-0.148, P<0.05), and attitude towards HPV vaccine positively affected intention to receive HPV vaccine (β=0.594, P<0.001). (4) Injunctive norms positively affected attitude towards HPV vaccine (β=0.362, P<0.001) and intention to receive HPV vaccine (β=0.420, P<0.001).